Constitutionalism in context / edited by David S. Law. - Law, David S. (Comparative constitutional law and policy., 2022)
With its emphasis on emerging and cutting-edge debates in the study of comparative constitutional law and politics, its suitability for both research and teaching use, and its distinguished and diverse cast of contributors, this handbook is a must-have for scholars and instructors alike. This versatile volume combines the depth and rigor of a scholarly reference work with features for teaching in law and social science courses. Its interdisciplinary case-study approach provides political and historical as well as legal context: each modular chapter offers an overview of a topic and a jurisdiction, followed by a case study that simultaneously contextualizes both. Its forward-looking and highly diverse selection of topics and jurisdictions fills gaps in the literature on the Global South as well as the West. A timely section on challenges to liberal constitutional democracy addresses pressing concerns about democratic backsliding and illiberal and/or authoritarian regimes.